IMPLEMENTASI KEBIJAKAN NUGROHO NOTOSUSANTO DALAM PENGAJARAN SEJARAH DI SMA (1983-1985) - Wira Syafutra (Universitas Negeri Yogyakarta, 2016)
This study aims to: (1) Explaining the background of life and thought Nugroho Notosusanto, (2) Explaining Nugroho Notosusanto policy in the implementation of the teaching of history in high school (1983-1985), and (3) Explaining the teaching of history in Senior High School (1983 to 1985 ). The method used is the method of historical research. Method according Kuntowijoyo historical research include: (1) selection of the topic, (2) the collection of resources, (3) verification, (4) interpretation, (5) historiography. The results showed that Notosusanto Nugroho is a historical figure who gave birth to a controversy of his thinking in the development of historical thought and history lessons at school (Senior High School). At the time served as Minister of Education and Culture, Nugroho implement a policy that is being debated for history courses. History is no longer integral in social studies (Social Studies), but stand-alone and appeared one more program that PSPB (National Struggle Historical Education). The reality of the application is indroktinasi through the lessons of history. The lesson of history serve as a means of legitimacy of power and the power of a group of the military. Keywords: Education Policy, Nugroho Notosusanto, History Teaching in Senior High School